APAKAH PERSEPSI RISIKO MEMPENGARUHI PERILAKU PASAR MODAL? BUKTI DARI PASAR EMERGING - Elviza (GREET, 2026)
This study provides robust empirical evidence that risk perception is a decisive driver of stock market behavior in emerging markets, extending behavioral finance theory beyond rational risk–return frameworks. Focusing on Indonesia as a representative emerging market, this research examines how investors’ subjective risk perceptions influence equity allocation, trading activity, and portfolio rebalancing decisions. Using survey data from 500 individual investors and market analysts and applying multiple regression analysis, the findings demonstrate that elevated risk perception significantly reduces stock allocation while simultaneously intensifying portfolio rebalancing behavior, indicating adaptive risk management rather than passive market exit. The results further reveal substantial heterogeneity in risk perception across demographic and socioeconomic groups, with education and income significantly moderating investment responses to perceived risk. These findings highlight that investor behavior in emerging markets is strongly shaped by psychological and informational factors amplified by institutional uncertainty and market volatility. By empirically integrating risk perception, behavioral responses, and investor characteristics, this study offers novel emerging-market evidence on the mechanisms through which perceived risk translates into market behavior and provides actionable implications for investors and policymakers seeking to strengthen market stability, investor resilience, and financial literacy frameworks.